Spatial assessment of water quality in Mananga River in Talisay City, Cebu, Philippines - Ronnel S. Melad; Raphael Luis V. Nonato; Dale Joseph Salazar; Mayzonee V. Ligaray; Angelo Earvin Sy Choi (Results in Engineering)
This paper focuses on the degradation of water quality in the Mananga River and aims to analyze spatial changes for the recommendation for rehabilitation. The use of ArcGIS and JMP software allows for the assessment of water quality and the identification of the causes of the contaminants coming from probable sources that are near the river. These activities are mainly rural areas and businesses that could have affected the degradation of the quality of the water in the river. By generating spatial distribution maps and conducting rapid profiling, this paper provides recommendations for rehabilitation. The significance of this paper lies in contributing to decision-making processes and the formulation of protective laws that can help in stop the degradation of the water quality of the river. Limitation includes the quarterly frequency of the water monitoring of the river. The results of this paper suggest that the Mananga River does not meet the requirements for DENR Administrative Order 2016-08 for type A rivers. The spatial distribution maps generated were able to visualize and identify the anthropogenic activities that may be affecting the water quality of the river. The DO showed a value from 0.0011 mg/L – 18.800 mg/L, BOD has a value ranging from 1.000 mg/L to 81.500 mg/L, 4.000 mg/L – 325.980 mg/L for TSS, and pH showed values from 7.400 to 8.800. These findings emphasize the need for government intervention and the development of automated river monitoring systems to facilitate testing and rehabilitation efforts.